"I would do it again": Past and present experiences of older lesbians. (3rd May 2020) - Averett, Paige; Pylant, Jordan; Craft, Katelyn; Ricks, Imani
ABSTRACT: Few studies have asked older lesbians to reflect on the primary experiences of their life. The following provides the responses of a nationally representative sample of 221 lesbians over the age of 55 to an open-ended question on anything they wanted to share. Through triangulated data analysis, resulting themes include the importance of the Women's Movement, coming out, as well as the role of discrimination. Underlying each of these were the importance of social connection and for some the increasing experience of disconnection. Implications for gerontology practice, policy, and future research are included.